DESIGN AND CHARACTERIZATION OF DIOSMIN-CYCLODEXTRIN COMPLEX AS A NOVEL TRANSDERMAL GEL - AMALHUSSEIN; HATEM SARHAN; AMAL S. ABU EL-ENIN (International Journal of Pharma and Bio Sciences, 2016)
Topical application of flavonoid has attracted interest due to their high vasoprotective and anti-inflammatory activities. The unfavorable physicochemical properties of diosmin (DSN) restrict its topical application. The impact of DSN/Cyclodextrins (CDs) complex formation on the improvement of the dissolution and permeation behavior of DSN has not so far been investigated. This study investigated the potential of DSN/HP-β-CD complex formation to enhance topical delivery and improve skin penetration of DSN. Physicochemical studies (Differential scanning colorimetric (DSC), infrared spectroscopy (IR), and x-ray diffractrometry) indicate successful complex formation at 1:2 molar ratios (MR) of DSN:DSN/HP-β-CD. Dissolution study indicates significant improvement of the dissolution rate of DSN from the of DSN:DSN/HP-β-CD complex compare to physical mixture (PM) or pure DSN. The highest release rates were found with gel containing inclusion complex compared to the gels containing pure DSN and its PM. Clinical study indicates pronounced effects of gel containing DSN/ HP-β-CD complex on the paw edema compared to pure DSN or PM. In conclusion, transdermal gel containing DSN/ HP-β-CD complex could be used as a new topical delivery system to improve DSN dissolution and permeation.